2019
DOI: 10.1002/jia2.25281
|View full text |Cite
|
Sign up to set email alerts
|

The burden of HIV among female sex workers, men who have sex with men and transgender women in Haiti: results from the 2016 Priorities for Local AIDS Control Efforts (PLACE) study

Abstract: Introduction Despite the higher risk of HIV among female sex workers (FSWs), men who have sex with men (MSM) and transgender women (TGW), these populations are under‐represented in the literature on HIV in Haiti. Here, we present the first nationally representative estimates of HIV prevalence and the first care and treatment cascade for FSWs, MSM and TGW in Haiti. We also examine the social determinants of HIV prevalence in these groups and estimate FSW and MSM population size in Haiti. Methods Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although STIs were more prevalent in participants who reported inconsistent use of condom and lubricant, the differences were not statistically significant as also reported by others 35. Access to lubricant and other STI prevention services are lacking among MSM in Haiti which might explain the inconsistent use of lubricant 8…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although STIs were more prevalent in participants who reported inconsistent use of condom and lubricant, the differences were not statistically significant as also reported by others 35. Access to lubricant and other STI prevention services are lacking among MSM in Haiti which might explain the inconsistent use of lubricant 8…”
Section: Discussionmentioning
confidence: 62%
“…The Haitian Ministry of Health and Population (French acronym MSPP) reported a HIV prevalence of 12.9% among MSM in 2014 4 7. The recent results from the 2016 Priorities for Local AIDS Control Efforts study showed lower estimates of HIV prevalence of 2.2% (95% CI: 0.9% to 5.3%) among MSM 8. This discrepancy in estimates of HIV burden among MSM in Haiti in two different reports, 2 years apart, is a result of the difficulty to reach the MSM populations.…”
Section: Introductionmentioning
confidence: 98%
“…MICBS are widely used in HIV-related research and more recently are being utilized in studies with TGD people (e.g., Madera et al, 2017). Specific MICBS include: DBS to assess systematic inflammation (Morgan, Taylor, Ryan, D'Aquila, & Mustanski, 2019), both DBS and saliva to access HIV incidence, prevalence and treatment efficacy (Flores, Brown, León, Sánchez, & Galea, 2018;Zalla, Herce, Edwards, Michel, & Weir, 2019), and finally DBS and hair samples to assess pre-exposure prophylaxis (PrEP) uptake and adherence (Gandhi et al, 2015(Gandhi et al, , 2017Marins et al, 2019). A number of studies have also established the feasibility of rapid HIV testing with TGD people with increased attention being paid to measuring the efficacy of PrEP (Grinsztejn et al, 2018).…”
Section: Hiv/aids and Global Healthmentioning
confidence: 99%
“…Many studies concerning the role of commercial sex intercourse in the HIV-1 epidemic have been based on classic epidemiological methods [12,13]. However, most of them lack direct genetic evidence of transmission linkages between FSWs and their clients or the influence of transmission relationships on the HIV-1 epidemic.…”
Section: Introductionmentioning
confidence: 99%